Nutritional management for post-stroke sarcopenia risk and multi-comorbidities patient via percutaneous endoscopic gastrotomy: a case report and review of the literature - Oliveira, Sofia; Martins, Beatriz; Pereira, Paula; Silva, Maria Leonor (Frontiers in Nutrition, 2024)
Stroke is a major cause of morbidity and mortality worldwide, often leading to complications such as malnutrition, dysphagia, and sarcopenia. We present the case of a 78-year-old male with a history of ischemic stroke and multiple comorbidities, who was underweight and weakened. Over a 10-month follow-up period, a percutaneous endoscopic gastrostomy (PEG) tube was placed, and nutritional management was carried out based on biochemical and nutritional status assessments. Anthropometric and blood biochemical parameters confirmed the need to adjust protein and energy intake to the patient’s requirements. Personalized nutritional intervention, including a caloric surplus and dietary adjustments, resulted in weight gain, improved muscle mass and biochemical blood parameters. This case report highlights the comprehensive nutritional management of a post-stroke patient to improve outcomes and quality of life.